PERKEMBANGAN PENDIDIKAN KEAGAMAAN PADA MASA PANDEMI COVID 19 DI PONDOK PESANTREN NURUL HUDA SINGOSARI - Muhammad Yazid Muzaqi; Azhar Haq; Moh Eko Nasrullah (VICRATINA, 2021)
The development of religious education during the COVID-19 PANDEMI at the Nurul Huda Singosari Islamic boarding school. The purpose of this study is (1) to describe the educational period before the covid 19 pandemic at the Nurul Huda Singosari Islamic boarding school (2) to describe the condition of education at the Nurul Huda Singosari Islamic boarding school during the covid 19 pandemic (3) to describe the obstacles to the educational process during the covid 19 pandemic in the Islamic boarding school. Nurul Huda Singosari Islamic Boarding School. The results of this study are (1) the education period before the covid 19 pandemic at the Nurul Huda Singosari Islamic boarding school using the lecture method, discussion method and using several learning strategies including, murojaah and tahfid (2) the educational conditions at the Nurul Huda Singosari Islamic boarding school during the covid pandemic. 19 has several steps to anticipate the spread of covid 19 at the Nurul Huda Singosari Islamic boarding school such as, checking and checking quick tests for students who want to return to the pesantren environment, conducting socialization about the covid 19 virus and its spread process, spraying disinfectant liquid in the pesantren environment, implementing lock download in Islamic boarding schools, etc. In terms of maintaining the safety and comfort of the students, the pesantren has taken several policies including maintaining cleanliness in the pesantren environment, applying bold and attractive formal learning, implementing face-toface special learning activities for pesantren, etc. (3) barriers to the educational process during the COVID-19 pandemic in Nurul Huda Singosari Islamic Boarding School, the process of adapting to new activities takes a lot of time, the students' lack of awareness of the dangers